Effects of mineralocorticoid receptor antagonists on the progression of diabetic nephropathy. Issue 4 (1st March 2017) - Sun, Li‐Jing; Sun, Yan‐Ni; Shan, Jian‐Ping; Jiang, Geng‐Ru
Abstract : The effects of mineralocorticoid receptor antagonists treatment in patients with diabetic nephropathy remain controversial now. Co‐administration of MRA and ACEI/ARB has beneficial effects on renal outcomes with increasing the incidence of hyperkalemia. Abstract: Aims/Introduction: We aimed to evaluate the potential benefits and adverse effects of adding a mineralocorticoid receptor antagonist (MRA) to angiotensin‐converting enzyme inhibitors (ACEI) and/or angiotensin receptor blockers (ARB), as standard treatment in patients with diabetic nephropathy. Materials and Methods: We scanned the Embase, PubMed and Cochrane Central Register of Controlled Trials databases for human clinical trials published in English until June 2016, evaluating renal outcomes in patients with diabetic nephropathy. Results: A total of 18 randomized controlled trials involving 1, 786 patients were included. Compared with ACEI/ARB alone, co‐administration of MRA and ACEI/ARB significantly reduced urinary albumin excretion and the urinary albumin–creatinine ratio (mean difference −69.38, 95% confidence intervals −103.53 to −35.22, P < 0.0001; mean difference −215.74, 95% confidence intervals −409.22 to −22.26, P = 0.03, respectively). A decrease of blood pressure was also found in the co‐administration of MRA and ACEI/ARB groups. However, we did not observe any improvement in the glomerular filtration rate. There was a significant increase in the risk of hyperkalemia on the addition of MRA to ACEI/ARB treatment (relative risk 3.74, 95% confidence intervals 2.30–6.09, P < 0.00001). Conclusions: These findings suggest that co‐administration of MRA and ACEI/ARB has beneficial effects on renal outcomes with increasing the incidence of hyperkalemia.